MEETING CHILDREN’S SPECIAL EDUCATIONAL NEEDS IN SCHOOL. A LITHUANIAN CASE - Alisauskas, Algirdas; Alisauskiene, Stefanija; Milteniene, Lina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article is been based on the research with the aim to reveal the features of pedagogical and special pedagogical support for pupils with special educational needs (SEN) as well as to assess the demand for changes in the mentioned field on the ground of the survey of Lithuanian pedagogues and professionals (in all 1518 respondents). The number of children with SEN educating in mainstream schools is increasing, however, not only involvement of pupils having diverse needs (including those having SEN) into mainstream education is important, but also qualitative analysis of the educational process and content too. The analysis of highlighted character of implementation of pedagogical and special pedagogical support as well as the demand for changes showed the main focuses for improvement: support to child in a classroom decreasing exclusion, involving other participants (peers, parents, volunteers etc.), using flexible models and strategies of support.